Implementation of Pojok Gizi to Improve Nutrition Knowledge and Monitor the Nutritional Status of University Students - Nadya Ulfa Tanjung (FKM UIN Sumatera Utara Medan, 2026)
College students represent a productive population undergoing a critical transition into adulthood. During this period, substantial changes in dietary patterns, physical activity, and lifestyle behaviors frequently occur, potentially influencing their nutritional status. Academic demands, limited time availability, and increased consumption of fast food are among the key factors contributing to the development of nutritional problems within this population. Therefore, effective promotive and preventive interventions are essential to enhance student’s awareness of the importance of maintaining their optimal individual nutritional status. Program Pojok Gizi is a community engagement initiative designed to provide nutritional status screening, dietary assessment, and nutrition education for university students. The program was implemented through anthropometric measurements, dietary assessment using the 24-hour dietary recall method, and face-to-face nutrition education and counselling. The findings demonstrated that participants gained a better understanding of their nutritional status and improved their knowledge of implementing the principles of a balanced diet in their daily lives. Furthermore, the program enhanced student’s awareness of the importance of adopting healthy dietary behaviors and routinely monitoring their nutritional status. Overall, Program Pojok Gizi has the potential to serve as an effective health promotion strategy for improving student’s nutritional awareness and supporting better health outcomes within the university setting.